MAKAN-MAKAN DALAM KELAMBU, DIVERSITY OF MELAYU-BUGIS TRADITION IN PONTIANAK, WEST KALIMANTAN - Sri Retno, Elza (Khatulistiwa, 2018)
The culture possessed by Bugis people in the equatorial city is very diverse, in each sub-district even has its own differences. Makan-makan Dalam Kelambu which was carried out in West Pontianak District which was a very densely populated location of Melayu-Bugis. More clearly the location is in Kelurahan Sungai Jawi Dalam, Jalan Srikaya. It was here that at that time had carried out a cultural activity called Makan-makan dalam Kelambu. This tradition is carried out by people who do celebrations and are carried out by Bugis people in general. But at that time the people who carried out the celebration were not only the original Bugis tribe, but also a mixture of Bugis Melayu tribes. This is what Melayu-Bugis people do in Makan-makan dalam Kelambu tradition. The tradition of Makan-makan Dalam Kelambu is a series of activities that are believed by Melayu-Bugis community to be carried out for safety and a form of gratitude to the Almighty God and avoid supranatural spirit disorder.